Avaliação de duas ferramentas para a representação das variáveis acústicas implicadas no vibrato da flauta. - Jessica Dalsant (2011)
This work investigated the flute vibrato, to determine which analytical tools that represent it in a more comprehensive way. Our aim is to use these tools to improve flute instrumental technic.After considering previously published works on this topic, it has been decided to focus this investigation on the following vibrato acoustical parameters: extent, rate, deviation from the fundamental frequency (F0), regularity and wave shape, attack end ending of the note, use of the vibrato in the attack and ending of the note, noises/ ghost clouds, vibrato and spectral envelope evolution in time. Two different types of tools were tested: first the spectrographic analysis program named SpectraPro, second an algorithm for the measure of vibratos fluctuations, proposed by the Physics and Electronics Departments of UFMG. Both tools are based based on the Fast Fourier Transform (FFT), but using different interfaces. Two types of samples have been evaluated: 1) long notes extracted from commercial recording 2) long notes from non commercial recordings, played live by different professional flutists in different dynamics and octaves. The same note was selected from a piece for solos flute, Syrinx, by Claude Debussy (1862-1918). The results of the application of these two tools indicated that the first one is more effective in measuring attack end ending of the note, noises/ ghost clouds, vibrato and spectral envelope evolution along the time, but its not precise in detecting rate and extent development in time. The second tool revealed to be more precise in measuring regularity, wave shape, rate and extent of F0. The analysis of different acoustical parameters involved in vibrato allows us to understand what kind of changes happens in flutes sound and timbre. To comprehend the various acoustical effects caused by vibrato in flute sound, means giving new technical and pedagogical possibilities for every flutist to improve the use, quality and flexibility of his/her vibrato and timbre. This can help to enrich the sound quality and the expressive possibilities of the flute.